Correction: Design, synthesis and anti-inflammatory effects of novel 9-O-substituted-berberine derivatives electronic supplementary information. Issue 4 (1st March 2016) - Huang, Mei-Yan; Lin, Jing; Huang, Zhi-Jian; Xu, Hong-Gui; Hong, Juan; Sun, Ping-Hua; Guo, Jia-Liang; Chen, Wei-Min
Abstract : Abstract : Correction for 'Design, synthesis and anti-inflammatory effects of novel 9- O -substituted-berberine derivatives' by Mei-Yan Huang et al., MedChemComm, 2016, DOI: ; Web:10.1039/c5md00577a .